Transcriptional and epigenetic mechanisms of promiscuous gene expression by thymic epithelial cells - Dhalla, F (2019)
The thymus is the primary lymphoid organ responsible for the generation and selection of a T-cell repertoire that is able to respond to foreign antigens whilst remaining tolerant to self. For the purposes of T-cell central tolerance induction thymic epithelial cells (TEC) express almost all protein coding genes in a process termed promiscuous gene expression (PGE), which is partly under the control of the Autoimmune Regulator (AIRE). Many aspects of the molecular mechanisms underlying PGE in TEC remain unclear. It has not yet been conclusively established whether PGE within single mTEC is a stochastic or coordinated process. The mechanisms that target AIRE to tissue-restricted genes (TRGs) are also incompletely defined, with previous studies suggesting that interaction partners of AIRE may localise AIRE to repressive epigenetic marks associated with TRGs in TEC. The first part of this study examines the transcriptional patterns associated with PGE in single mTEC. Analysis of the transcriptomes of 6,894 single mTEC revealed 50 robustly defined co-expression groups supporting the hypothesis that PGE in individual mTEC is a highly ordered process. The second part of this study addresses the role of a putative AIRE interaction partner, Chromodomain-helicase-DNA-binding protein 4 (CHD4), in TEC biology. Using a variety of cellular and molecular tools, CHD4 was demonstrated to play important roles in TEC development, architectural organisation and function. In particular, CHD4 was found to cooperate functionally with AIRE to induce the promiscuous expression of AIRE-induced TRGs found in particularly repressive chromatin contexts and was consequently required for proper T-cell central tolerance induction.